An experimental system for electrical and mechanical education: Micro hydro power plant prototype - Ozdemir, Mahmut Temel; Orhan, Ahmet (Elsevier Science Bv, 2012)
In this study, an experimental system has been designed in order to use for education of the technical staff at this important plants. The implemented system has included realistically whole the parts of a micro hydro power plant (MHPP). MHPP has been controlled by PLC. The reason why PLC has been chosen is to try the new control methods and its durability. The classical control, the fuzzy control, the artificial neural network and hybrid applications could be carried out by PLC. (c) 2012 Published by Elsevier Ltd.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Micro Hydro PowerPlant; Energy Produced; PLC; Fuzzy Logic